Evolution of the sewage treatment plant model SimpleTreat: Applicability domain and data requirements. (28th May 2013) - Franco, Antonio; Struijs, Jaap; Gouin, Todd; Price, Oliver R
Abstract SimpleTreat 3.1 is the sewage treatment plant (STP) model implemented in the European Union (EU) framework for the environmental risk assessment of chemicals. The model was originally designed for neutral hydrophobic chemicals, whereas many substances currently under regulatory scrutiny, are ionizable at environmental pH. Although the model has been adapted to describe ionization (SimpleTreat 3.1), the fate of organic ions is limited to the unbound aqueous phase, which seriously restricts the applicability domain. New regressions were implemented to estimate the sludge–water partition coefficient normalized to organic carbon (KOC) of monovalent acids and bases from the octanol–water partition coefficient (KOW), the dissociation constant (pKa) and the pH. We evaluated the updated model (SimpleTreat 3.2) with 10 test chemicals by comparing predictions with monitoring data collected from the literature. Test chemicals were specifically selected to challenge the applicability domain and to cover a wide range of functionality and physical–chemical properties. Although predicted effluent concentrations are generally conservative, SimpleTreat 3.2 provides reasonable estimates for use in lower‐tier risk assessment for neutral and monovalent ionizable chemicals. The accuracy of the new KOC regressions is acceptable for monovalent acid but is lower for bases, for which measured sludge KOC is highly recommended. Measured KOC are also recommended for ionic surfactants and necessary for organic ligands, which may limit the applicability of SimpleTreat using a basic input data set. The conservative nature of model estimates reflects the default worst case, non‐numerical parameterization of biodegradation rates and the assumption that biodegradation is limited to the unbound aqueous phase. The potential of refining the description of biodegradation using higher tier simulation tests is explored in a parallel article (Franco et al. this issue). Integr Environ Assess Manag 2013;9:560–568. © 2013 SETAC